2010
DOI: 10.3758/s13421-010-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Automatic processing influences free recall: converging evidence from the process dissociation procedure and remember-know judgments

Abstract: Dual-process theories of retrieval suggest that controlled and automatic processing contribute to memory performance. Free recall tests are often considered pure measures of recollection, assessing only the controlled process. We report two experiments demonstrating that automatic processes also influence free recall. Experiment 1 used inclusion and exclusion tasks to estimate recollection and automaticity in free recall, adopting a new variant of the process dissociation procedure. Dividing attention during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 73 publications
9
58
0
Order By: Relevance
“…Taken together the results suggest that familiarity also contributes to associative cued recall. Thus, the results are consistent with prior results showing cued recall tasks can be supported at least in part by familiarity (Gruneberg & Monks, 1974; Starns & Ratcliff, 2008; McCabe et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together the results suggest that familiarity also contributes to associative cued recall. Thus, the results are consistent with prior results showing cued recall tasks can be supported at least in part by familiarity (Gruneberg & Monks, 1974; Starns & Ratcliff, 2008; McCabe et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…One prior study that examined this issue found that recollection, but not familiarity, correlated with free recall performance (Quamme, Yonelinas, Widaman, Kroll, & Sauve, 2004). However, there is evidence that associative cued recall performance is related to ‘feelings of knowing’ (Gruneberg & Monks, 1974), that cued recall can be influenced by both controlled recollective processes and automatic familiarity processes (McCabe, Roediger, & Karpicke, 2011). Moreover, both recollection and familiarity are correlated with associative recognition, a form of recognition thought to depend more on recollection (Starns & Ratcliff, 2008).…”
Section: Experiments 1 Discussionmentioning
confidence: 99%
“…These results support previous research that suggests that familiarity and conceptual priming rely on a similar underlying process (Yonelinas, 2002), and argue against models that postulate that explicit and implicit memory reflect fundamentally separate processes (e.g., . In addition, the cued recall results are consistent with research demonstrating that both recollection and familiarity support associative recall (McCabe et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Graf, Squire, and Mandler (1994) found that amnesic participants' performance was 14% on free recall tests, 58% on a word-stem cued recall test, and 57% on an indirect word-stem completion test. One way of interpreting these participants' achievements in free recall and cued recall tests is in terms of unconscious (automatic) influences of prior experience (see McCabe, Roediger, & Karpicke, 2011). Under this interpretation, these results indicate that automatic influences can quite strongly affect performance in cued recall and to a much lesser extent in free recall.…”
Section: Discussionmentioning
confidence: 94%